A "Step–Ramp–Step" Protocol to Identify the Maximal Metabolic Steady State. Issue 9 (September 2020) - IANNETTA, DANILO; INGLIS, ERIN CALAINE; POGLIAGHI, SILVIA; MURIAS, JUAN M.; KEIR, DANIEL A.
ABSTRACT: The oxygen uptake (V[Combining Dot Above]O2 ) at the respiratory compensation point (RCP) closely identifies with the maximal metabolic steady state. However, the power output (PO) at RCP cannot be determined from contemporary ramp-incremental exercise protocols. Purpose: This study aimed to test the efficacy of a "step–ramp–step" (SRS) cycling protocol for estimating the PO at RCP and the validity of RCP as a maximal metabolic steady-state surrogate. Methods: Ten heathy volunteers (5 women; age: 30 ± 7 yr; V[Combining Dot Above]O2max : 54 ± 6 mL·kg −1 ·min −1 ) performed in the following series: a moderate step transition to 100 W (MOD), ramp (30 W·min −1 ), and after 30 min of recovery, step transition to ~50% POpeak (HVY). Ventilatory and gas exchange data from the ramp were used to identify the V[Combining Dot Above]O2 at lactate threshold (LT) and RCP. The PO at LT was determined by the linear regression of the V[Combining Dot Above]O2 versus PO relationship after adjusting ramp data by the difference between the ramp PO at the steady-state V[Combining Dot Above]O2 from MOD and 100 W. Linear regression between the V[Combining Dot Above]O2 –PO values associated with LT and HVY provided, by extrapolation, the PO at RCP. Participants then performed 30-min constant-power tests at the SRS-estimated RCP and 5% above this PO. Results: All participants completed 30 min of constant-power exercise at the SRS-estimated RCP achieving steady-state V[Combining Dot Above]O2 of 3176 ± 595 mL·min −1 that was not different ( P = 0.80) from the ramp-identified RCP (3095 ± 570 mL·min −1 ) and highly consistent within participants (bias = −26 mL·min −1, r = 0.97, coefficient of variation = 2.3% ± 2.8%). At 5% above the SRS-estimated RCP, four participants could not complete 30 min and all, but two exhibited non–steady-state responses in blood lactate and V[Combining Dot Above]O2 . Conclusions: In healthy individuals cycling at their preferred cadence, the SRS protocol and the RCP are capable of accurately predicting the PO associated with maximal metabolic steady state. Abstract : Supplemental digital content is available in the text.